Hypoxis limicola and H. uniflorata (Hypoxidaceae) deserve species rank: multiple new lines of evidence - Niemann, Hendrik J.; Coetzer, Dewald J.; Glennon, Kelsey L. (Phytotaxa, 2023)
Hypoxis, the largest genus within the Hypoxidaceae, has its primary centre of diversity and endemism within southern Africa. The taxonomy of the genus has always presented a challenge due to a lack of distinct diagnostic characters that readily define species and infraspecific taxa—with polyploidy, hybridization, and apomixis thought to contribute substantially to these challenges. This holds true for the informally designated Hypoxis parvula species complex—a group of five soft-leaved taxa (H. parvula var. parvula, H. parvula var. albiflora, H. limicola, H. uniflorata, and H. membranacea) that have been treated as distinct by some authors and have variously been reduced to synonyms by others. Here, the taxonomic status of lineages within this complex is evaluated using flow cytometry, morphological, environmental, and molecular data. Specifically, it is evaluated whether there is sufficient support to resurrect Hypoxis limicola and to uphold the little-known H. uniflorata. Differences in relative genome size estimates between H. limicola and the H. parvula varieties, as well as environmental data, suggest that H. limicola exists outside the ecological habitat of both H. parvula varieties, which supports the distinctness of these two species. Results from the phylogenetic analysis based on cpDNA regions (rbcL, trnS-G, and trnL-F) showed that H. limicola, H. parvula, and H. uniflorata formed distinct, well supported clades within Hypoxis. Hypoxis membranacea did not resolve with any members of the H. parvula species complex, but instead formed a clade with H. angustifolia—a taxon with which it overlaps morphologically and ecologically, and with which it is thought to hybridize. Collectively, the data supports reinstatement of H. limicola and recognition of H. uniflorata as a distinct species. Descriptions with updated notes on habitat, distribution, relationships, and diagnostic features are provided for the focal taxa in this study, together with an identification key.